Diffuse Large B‐Cell Lymphoma with Secondary Hemophagocytic Lymphohistiocytosis Presenting as Acute Liver Failure. Issue 1 (2017) - Patel, Ruchi; Patel, Haren; Mulvoy, William; Kapoor, Sumit
ABSTRACT : N/A: Hemophagocytic lymphohistiocytosis (HLH) and newly diagnosed malignant infiltration of liver are rare presentations of acute liver failure associated with poor prognosis. We report a case of a patient with acute liver failure caused by malignant infiltration by diffuse large B‐cell lymphoma and secondary HLH.